2022
DOI: 10.1002/cbdv.202200022
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic and Antiurolithic Effect of Garcinia humilis (Vahl) C.D. Adams Leaves, a Medicinal Plant Native to South American Countries

Abstract: This study evaluated the diuretic and antiurolithic effect of methanolic extract (MEGHL), dichloromethane (DCM), and ethyl acetate (EtA) fractions obtained from the leaves of Garcinia humilis, a medicinal plant known as achachairu and native to South American countries such as Bolivia, Peru, and Brazil. For the analysis of diuretic effect, the female rats received the treatment with MEGHL (3, 10, and 30 mg/kg), DCM (1, 3 and 10 mg/kg), EtA (1, 3, and 10 mg/kg), hydrochlorothiazide (HCTZ; 10 mg/kg), or vehicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also referred to as “achachairu”, this evergreen tree belongs to the Clusiaceae family and has been traditionally utilized by indigenous communities for its medicinal benefits. Preparations obtained from different parts of this plant have already been the subject of studies revealing antimicrobial [ 15 ], gastroprotective [ 16 ], anti-inflammatory [ 17 ], and diuretic [ 18 ] properties. In the present study, we extended these actions to understand the benefits of this plant in mechanisms that contribute to the control of blood pressure, since the demonstration of diuretic activity has already opened this promising perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Also referred to as “achachairu”, this evergreen tree belongs to the Clusiaceae family and has been traditionally utilized by indigenous communities for its medicinal benefits. Preparations obtained from different parts of this plant have already been the subject of studies revealing antimicrobial [ 15 ], gastroprotective [ 16 ], anti-inflammatory [ 17 ], and diuretic [ 18 ] properties. In the present study, we extended these actions to understand the benefits of this plant in mechanisms that contribute to the control of blood pressure, since the demonstration of diuretic activity has already opened this promising perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, recent studies have demonstrated the antiur- olithic effect on plant species or isolated compounds using CaOx model. [3,25,26] The next step of this study was to evaluate the possible effect of HEMN on the formation of calcium oxalate (CaOx) crystals in vitro (Figure 2). The results showed that potassium citrate (KC; 10 mg/mL), the positive control group, decreased the total number of CaOx crystals when compared to VEH sample (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Nirumand et al., (2018) [4] described several studies on using medicinal plants to prevent kidney stones. Besides, recent studies have demonstrated the antiurolithic effect on plant species or isolated compounds using CaOx model [3,25,26] …”
Section: Resultsmentioning
confidence: 99%